Análisis comparativo de la gestión de control aplicado en la administración tributaria y propuesta de optimización a la administración ecuatoriana - Amoroso Garcés, Sylvia María (2017)
This research aims to generate in the social environment a different approach of fiscal policy, the same that promotes social and financial revitalization, in which citizen alignment is vital. The goal is to establish an efficient collection of information which establishes the way how to generate a model of citizen participation and integration, thus promoting a new citizen behavior and socioeconomic change to promote dynamism and productivity in all productive and commercial aspects. The proposal is to generate a distinctive structure in management control with cross and the internal databases which allow not only minimizing evasion, but institutional efficiency in the service of the taxpayer.